“EFECTO DEL CRECIMIENTO ECONÓMICO EN EL DESARROLLO HUMANO, UN ESTUDIO CON DATOS PANEL PARA AMERICA LATINA” - Chamba Cuje, Emily Thays (2021)
Talking about human development is synonymous with a dignified life for the individuals of a society, where adequate and quality education levels are guaranteed, timely medical care for citizens, with the necessary infrastructure in both cases; likewise, sufficient income for families to meet their needs. The research aims to study the effect of economic growth on human development for 11 Latin American countries, in the period 1995-2018, to determine this effect, regression techniques were used through a GLS model and cointegration tests with panel data, which were provided by the World Bank (2019) and UNDP (2019). The results of the GLS model indicate that there is a strong and direct relationship between economic growth and human development, in terms of the control variables added to the model, these are presented in a positive way, but their significance is not strong. Likewise, cointegration tests were used, which verify the existence of a balance in the short and long term. Furthermore, the results indicate that the explanatory variables directly affect the dependent variable; that is to say, to human development. Finally, it is recommended since it is of vital importance that governments strengthen their economies through the application of policies focused on competitiveness, economic dynamism, economic openness, foreign investment, local reinvestment and strengthening of the productive apparatus in general.